Temperature-dependent dynamics of energy stores in Drosophila - Diana Knoblochová; Malleswara Dharanikota; Martina Gáliková; Peter Klepsatel (BMC Biology)
Abstract Background Understanding how ectotherms manage energy in response to temperature is crucial for predicting their responses to climate change. However, the complex interplay between developmental and adult thermal conditions on total energy stores remains poorly understood. Here, we present the first comprehensive quantification of this relationship in Drosophila melanogaster, a model ectotherm, across its entire thermal tolerance range. To account for potential intraspecific variation, we used flies from two distinct populations originating from different climate zones. Utilizing a full factorial design, we assessed the effects of both developmental and adult temperatures on the amount of key energy macromolecules (fat, glycogen, trehalose, and glucose). Importantly, by quantifying these macromolecules, we were able to calculate the total available energy. Results Our findings reveal that the dynamic interplay between developmental and adult temperatures profoundly influences the energy balance in Drosophila. The total energy reserves exhibited a quadratic response to adult temperature, with an optimal range of 18–21 °C for maximizing energy levels. Additionally, the temperature during development considerably affected maximum energy stores, with the highest reserves observed at a developmental temperature of approximately 20–21 °C. Deviations from this relatively narrow optimal thermal range markedly reduced energy stores, with each 1 °C increase above 25 °C diminishing energy reserves by approximately 15%. Conclusions This study highlights the critical and interacting roles of both developmental and adult thermal conditions in shaping Drosophila energy reserves, with potentially profound implications for fitness, survival, and ecological interactions under future climate scenarios.